Design and Implementation of Hybrid-Climbing Legged Robot - Hassan, Mustafa Y.; Rashid, Mofeed T.; Abdulaali, Ali H. (Iraqi Journal for Electrical and Electronic Engineering, 2019)
In this paper, the hybrid-climbing legged robot is designed, implemented, and practically tested. The robot has four legs arranged symmetrically around the body were designed for climbing wire mesh fence. Each leg in robot has 3DOF which makes the motion of the robot is flexible. The robot can climb the walls vertically by using a unique design of gripper device included metal hooks. The mechanism of the movement is a combination of two techniques, the first is the common way for the successive movement like gecko by using four limbs, and the second depending on the method that used by cats for climbing on the trees using claws, for this reason, the robot is named hybrid-climbing legged robot. The movement mechanism of the climbing robot is achieved by emulating the motion behavior of the gecko, which helped to derive the kinematic equations of the robot. The robot was practically implemented by using a microcontroller for the mainboard controller while the structure of the robot body is designed by AutoCAD software. Several experiments performed in order to test the success of climbing on the vertical wire mesh fence.